Odpowiedź :
a₁=3 cm
r = 2
Sn=765
Sn = (a₁+an)/2 i an=a₁+ (n-1)×r
Sn = (2a₁ + (n-1)×r)/2
765 = (2×3 + (n-1)×2)/2
1530 = 6 + 2n - 2
1526 = 2n
n = 763
r = 2
Sn=765
Sn = (a₁+an)/2 i an=a₁+ (n-1)×r
Sn = (2a₁ + (n-1)×r)/2
765 = (2×3 + (n-1)×2)/2
1530 = 6 + 2n - 2
1526 = 2n
n = 763
K₄=14 610
p=3%
n=2007-2003=4
K₄=K(1+p/100)⁴
14610=K(1+0,03)⁴
14610=K*1,03⁴
14610=1,12550881K
K≈12981 ilość w 2003
2.z ciągu geometrycznego
a₁=3
q=2
Sn=765
Sn=[a₁(1-q^n):(1-q)]
765=[3(1-2^n):(1-2)]
765=3(1-2^n):(-1)
-765=3(1-2^n)
-255=1-2^n
-256=-2^n
256=2^n 256=2⁸
2⁸=2^n
n=8
odp.było 8 odcinków
p=3%
n=2007-2003=4
K₄=K(1+p/100)⁴
14610=K(1+0,03)⁴
14610=K*1,03⁴
14610=1,12550881K
K≈12981 ilość w 2003
2.z ciągu geometrycznego
a₁=3
q=2
Sn=765
Sn=[a₁(1-q^n):(1-q)]
765=[3(1-2^n):(1-2)]
765=3(1-2^n):(-1)
-765=3(1-2^n)
-255=1-2^n
-256=-2^n
256=2^n 256=2⁸
2⁸=2^n
n=8
odp.było 8 odcinków